Effect of synthesis condition on the structural features of ni-ce bimetallic catalysts supported on functionalized multi-walled carbon nanotubes - Nur Syahidah Afandi,; Mehrnoush Khavarian,; Abdul Rahman Mohamed, (Penerbit Universiti Kebangsaan Malaysia, 2019)
In this paper, screening study in regards to preparation of functionalized multi-walled carbon nanotubes (FMWNT)-supported bi-metallic catalyst is discussed. Functional groups such as hydroxyl and carboxylic acid are introduced on multi-walled carbon nanotubes (MWCNT) surface using acid treatment method with the aid of probe-type ultrasonication. It is done by varying the concentration of nitric acid (HNO3) and sulphuric acid (H2SO4), acid volume ratio and treatment duration. Catalysts with different ratios of cerium and nickel nanoparticles which are either loaded inside or outside of MWCNT were prepared via ultrasonic-assisted co-precipitation method (NiCe/CNT). This is done to study the effect of cerium loadings. The characterization of the FMWNT and catalysts are carried out using transmission electron micrographs (TEM), Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), Brunauer-Emmett-Teller (BET), X-ray diffraction (XRD), and Raman spectroscopy. The results showed that the treatment in concentrated HNO3/H2SO4 with volume ratio of 3:1 for 8 h was the most suitable condition to generate large amount of surface oxygen group with minimal defects. The observations for each used condition were discussed thoroughly. Decoration of MWCNT with different metal loadings resulted in different distribution and dispersion of metal on nanotubes surface.